A Polyphenol-Rich Extract of Olive Mill Wastewater Enhances Cancer Chemotherapy Effects, While Mitigating Cardiac Toxicity - Albini, Adriana; Festa, Marco M. G.; Ring, Nadja; Baci, Denisa; Rehman, Michael; Finzi, Giovanna; Sessa, Fausto; Zacchigna, Serena; Bruno, Antonino; Noonan, Douglas M. (Frontiers in Pharmacology, 2021)
Cardiovascular toxicities still remain one of the most undesirable side effects in cancer patients receiving chemotherapy. Extra-virgin olive oil (EVOO) is rich in cancer preventive polyphenols endowed with anti-inflammatory, antioxidant activities which could exert protective effects on the heart cells. One very interesting derivative of EVOO preparation is represented by purified extract form waste waters. Here, we investigated the anti-cancer activity when combined with chemotherapeutics as well as potential cardioprotective activities of a polyphenol-rich extract from waste product of the EVOO, named A009. Mice bearing prostate cancer (PCa) xenografts were treated with cisplatin with and without A009. Tumor cell growth was reduced by cis and by A009 and further hindered by the combination. Hearts of mice were analyzed, and the mitochondria were studied by transmission electron microscopy. A protection activity by A009 was observed. To confirm the in vivo data, tumor cell lines and rat cardiomyocytes were treated with cisplatin in vitro with and without A009. A009 enhanced cisplatin and 5FU reduced tumor cell growth while did not further affect co-treated rat cardiomyocytes. Another frequently used chemotherapeutic agent 5-fluorouracil (5FU), was also tested in this assay, observing a similar effect. A009 extract cardioprotective effects towards 5 FU chemotherapy were further investigated in vitro, using cardiomyocytes freshly isolated from mice pups, treated with 5-fluorouracil and A009. Wastewater extract mitigated toxicity of the fluoropyrimidine. In vivo, we found synergisms of A009 and cisplatin in prostate cancer treatment. Hearts of mice xenografted with PCa cell lines and receiving co-treatments of A009 extracts along with cisplatin had reduced mitochondria damage compared to chemotherapy alone, indicating a cardioprotective role. A009 in vitro was additive to cisplatin and 5FU to reduce cancer cell growth while did not further affect rat cardiomyocytes cell cultures treated with cisplatin and 5FU. The A009 extract also rescued the proliferation rate of neonatal murine cardiomyocytes treated with 5-Fluorouracil. Our study demonstrates that the polyphenol rich purified A009 extracts enhances the effect of chemotherapy in vitro and in vivo but mitigates effects on heart and heart cells. It could therefore represent a potential candidate for cardiovascular prevention in patients undergoing cancer chemotherapy.